2022
DOI: 10.1021/acs.jchemed.2c00764
|View full text |Cite
|
Sign up to set email alerts
|

Complexometric Titration of Bismuth in Over-the-Counter Stomach Relief Products

Abstract: Three direct complexometric titration methods for bismuth subsalicylate determination in over-the-counter stomach relief caplets and liquids are presented, as well as a UV–vis assay, for use in student laboratories. The main difference between titration methods is the choice of indicator; either xylenol orange (XO), pyrocatechol violet (PV), or potassium iodide (KI) is used. These methods are simple and safe, making this experiment desirable in a general chemistry or analytical laboratory to relate real-world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Beyond traditional buret experiments, a plethora of intriguing experiments can be devised by coupling burets with other gadgets. For instance, titration experiments can be amalgamated with mobile phones, , virtual experimental software for simulation exercises, or even practical applications for scientific research projects. These experiments are certainly innovative and captivating, yet students yearn for an experimental program that comprehensively illustrates the entire spectrum of titration. In other words, they desire an experiment that unveils the titration process in its entirety, showcasing its various dimensions, practical applications, and multiple layers.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond traditional buret experiments, a plethora of intriguing experiments can be devised by coupling burets with other gadgets. For instance, titration experiments can be amalgamated with mobile phones, , virtual experimental software for simulation exercises, or even practical applications for scientific research projects. These experiments are certainly innovative and captivating, yet students yearn for an experimental program that comprehensively illustrates the entire spectrum of titration. In other words, they desire an experiment that unveils the titration process in its entirety, showcasing its various dimensions, practical applications, and multiple layers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, what students should do is integrate various skills, rather than collect certificates. It is particularly necessary to add realistic experimental projects in experimental teaching. , This will also enable students to better prepare for real-world laboratory work and research, thereby achieving better learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous educational publications have illustrated the value of incorporating real-world sample analysis to bridge the gap between theoretical concepts and students’ everyday experiences. Furthermore, several applications of the titration techniques to real-world samples have been published in this Journal. , These works showed that engaging in meaningful tasks that mimic real-world situations faced by experts in their respective fields allowed students a greater comprehension and integration of theoretical and experimental concepts.…”
mentioning
confidence: 99%